Pulmonary blood flow measured by inspiratory inert gas concentration forcing oscillations - Williams, E; Sainsbury, M; Sutton, L; Xiong, L; Black, A; Whiteley, J; Gavaghan, D; Hahn, C (1998)
The aim of this study was to discover if the forced inspired inert gas sinewave technique could be used to measure pulmonary blood flow, using nitrous oxide as the indicator gas, following inotropic stimulation of the heart by dobutamine, in the presence of a constant alveolar ventilation. Cardiac output (range 1-4.5 L min(-1)) was measured in six dogs by thermodilution and by calculation from the sinusoidal expired partial pressures of argon and nitrous oxide using: (i) analytical equations and a conventional continuous ventilation three-compartment lung model, which did not include recirculation; and